Prevalence of human papillomavirus antibodies in young female subjects in England - Jit, M; Vyse, A; Borrow, R; Pebody, R; Soldan, K; Miller, E (British journal of cancer, 2007)
Sera from 1483 female subjects in England aged 10–29 years were tested. The age-standardised seroprevalence was 10.7% (95% confidence intervals 9.0–12.3) for human papillomavirus (HPV) 6, 2.7% (1.8–3.6) for HPV 11, 11.9% (10.2–13.6) for HPV 16, 4.7% (3.5–5.8) for HPV 18, and 20.7% (18.6–22.7) for any of the four types.